Modulation of digestibility of canine food using enzyme supplement: an in vitro simulated semi-dynamic digestion study - Jadhav, Swati; Gaonkar, Tejal; Joshi, Mithila; Rathi, Abhijit (Frontiers in Veterinary Science, 2023)
Digestibility and nutrient availability are important parameters while estimating the nutritional quality of the pet food. We have developed a simulated semi-dynamic in-vitro canine digestion model to evaluate the digestibility of the dry extruded canine food. Canine food was assessed for digestible energy, dry matter digestibility, protein digestibility, non-fibrous carbohydrate (NFC) digestibility, and total antioxidant capacity (TAC) in the absence and presence of enzyme blend (DigeSEB Super Pet). Enzyme blend supplementation in the canine food was found to increase the dry matter digestibility (18.7%, p<0.05), digestible energy (18.1%, p<0.05), protein digestibility (11%, p<0.1), and reducing sugar release (106.3%, p<0.005). The release of low molecular weight peptides (48.7%) and essential amino acids (15.6%) were increased within 0.5 h of gastrointestinal digestion due to enzyme blend supplementation. Furthermore, TAC of the digesta was also increased (8.1%, p<0.005) in the canine food supplemented with enzyme blend. Overall, supplementation of enzyme blend in the canine food is an effective strategy to enhance the food digestibility and nutrients availability for absorption.